Watchdog role of media an exploratory study of martial law-oriented opinion items of newspapers in Davao City - Caballero, Khyle Khwences C.; Comidoy, Merle Dawn S. (2019)
This study examined the watchdog role of two local newspapers in Davao City in their editorials and columns about Martial law. The study did this by using a watchdog index (WDI) with (1) Information and (2) Criticism as the main two dimensions of assessment. The watchdog role of media was defined as the role of media in checking on the powerful sectors of society, including the government. As there is a thin line between the information and analysis roles of media, an overlap amongst the two encapsulates a vital part of their watchdog role. This study then examined the opinion items (editorial and columns) of each newspaper organization, as most editorials and commentaries are analytical in nature. A comparative content analysis on how Martial Law is framed by the two local newspapers was also done in order to examine similarities and differences and identify trends amongst them. The main findings showed that the editorials and columns of Sunstar Davao and Mindanao Times did not play their watchdog role satisfactorily. Comparing the watchdog role dimensions of Information and Criticism, the results showed that both the editorials and columns were more informative and less critical.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019